Developing Environment Friendly Behaviour among Adolescents: Role of Intervention - Kumari, Chandra; Awasthi, Seema (INDIAN EDUCATIONAL REVIEW, 2009)
The influence of environmental destruction on modern life has been a globally critical problem. Industrialised countries degrade the environment by insatiable consumption of resources and intense production of waste. Population Growth in many developing countries puts damaging pressure on the planet. Therefore, if we want to manage our earth we must make people environmentally educated to develop environment friendly behaviour. Environment friendly behaviour is any action of individual or group directed toward the remediation of environment problems. Present study attempts to assess the impact of intervention on environment friendly behaviour amongs adolescents. The data were collected from a sample of 150 IX and X grade adolescents by using environmental responsibility assessment inventory and consciousness about pollution scale, developed by Dr. Sandhya Gihar, Kukreti & Shah. Thirty students were selected as sub sample for intervention.. The study has revealed that there is significant impact of intervention on adolescents’ consciousness about environment pollution and environment friendly behaviour. The study has not found gender difference on environment friendly behaviour and consciousness about pollution among boys and girls.